Transmission of human capital across four generations: Intergenerational correlations and a test of the Becker-Tomes model - Mikael Lindahl; Mårten Palme; Sofia Sandgren Massih; Anna Sjögren (Uppsala University, Department of Economics, 2011)
Most previous studies on intergenerational transmission of human capital are restricted to two generations - between the parent and the child generation. In this paper we investigate if there is an independent effect of the grandparent and the great grandparent generations in this process. We use a dataset where we are able to link individual measures of life time earnings for three generation and data on educational attainments of four generations. We first do conventional regressions and transition matrices for life time earnings measures and educational attainments adding variables for the grandparent and great grandparent generations, respectively. We find that grandparents and even great grandparents significantly influence earnings and education. We then estimate the so called Becker-Tomes model using the educational attainment of the great grandparent generation as an instrumental variable. We fail to find support for the model's predictions.
urn:nbn:se:uu:diva-164682
Keywords: D31; J62; 330; intergenerational income mobility; earnings distribution; income inequality; Lebenseinkommen; Soziale Mobilität; Intergenerationale Übertragung; Einkommensverteilung; Schweden